Disseminated Intravascular Coagulation, Hemoperitoneum, and Reversible Ischemic Neurological Deficit Complicating Anaphylaxis to Prophylactic Antibiotics during Cesarean Delivery: A Case Report and Review of Literature - Mostafa A. Borahay; Hassan M. Harirah; Gayle Olson; Gokhan S. Kilic; Sinem Karipcin; Gary D.V. Hankins (Thieme Medical Publishers, Inc., 2011)
Routine use of prophylactic antibiotics reduces the risk of postcesarean fever and infections by over 50% in both nonelective and elective (scheduled) procedures. Although anaphylaxis to prophylactic antibiotics is rare, potentially fatal complications might occur. Herein, we present a case where disseminated intravascular coagulation and reversible ischemic neurological deficit complicated anaphylactic reactions to prophylactic antibiotics administered during cesarean delivery. A 27-year-old gravida 9, para 7 at 392/7 weeks underwent elective repeat cesarean delivery and bilateral tubal ligation. Her surgery was complicated by intraoperative hypotension, generalized itching, and urticarial skin rash consistent with anaphylactic reaction upon administering prophylactic cefazolin. In the recovery room, she continued to be hemodynamically unstable despite energetic resuscitation. Hemoperitoneum was suspected, and laboratory evaluation indicated disseminated intravascular coagulation. Abdominal exploration revealed massive hemoperitoneum, but there was no source of active bleeding noted. The postoperative course was complicated by reversible ischemic neurological deficit, which resolved on expectant management. Disseminated intravascular coagulation and reversible ischemic neurological deficit may complicate anaphylactic reaction to prophylactic antibiotics administered during cesarean delivery. Immediate recognition and intervention is crucial for a successful outcome.